Voice Onset Time in Children - P, Kushal Raj; NP, Nataraja (Journal of All India Institute of Speech and Hearing)
The present study reports VOT for stop consonants and in children. 100 male and female children belonging to 5 age groups, ranging from 4-12 years were used to elicit 3 sentences as responses to 3 picture cards. The sentences elicited as responses consisted of the consonants /p/ and in initial position and /t/ in medial position of the words. These were analyzed using High Resolution Signal Analyzer (B and K 2033) to obtain VOT. The results showed that there was no significant difference in VOT between males and females. Between different age groups of the same sex, except for the children of 4-5 years, no other group had shown significantly different VOT values.